2021
DOI: 10.3390/pathogens10030305
|View full text |Cite
|
Sign up to set email alerts
|

The Latest Research on RT-QuIC Assays—A Literature Review

Abstract: The misfolding of proteins such as the prion protein, α-synuclein, and tau represents a key initiating event for pathogenesis of most common neurodegenerative disorders, and its presence correlates with infectivity. To date, the diagnosis of these disorders mainly relied on the recognition of clinical symptoms when neurodegeneration was already at an advanced phase. In recent years, several efforts have been made to develop new diagnostic tools for the early diagnosis of prion diseases. The real-time quaking-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 65 publications
1
16
0
1
Order By: Relevance
“…Freshly prepared sCJD VV2 BH showed positivity both in RT-QuIC and western blot. The RT-QuIC assay of 92 post-mortem archival BH samples showed 97.4% sensitivity and 100% specificity, comparable to previously published results [12]. Our data suggest that BHs originally prepared for definitive post-mortem diagnosis and frozen for several years are generally suitable for RT-QuIC retrospective studies; however, the presence of one negative sample confirmed that long-term storage of BH, in the form of detergent lysate, may occasionally lead to a loss of RT-QuIC seeding activity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Freshly prepared sCJD VV2 BH showed positivity both in RT-QuIC and western blot. The RT-QuIC assay of 92 post-mortem archival BH samples showed 97.4% sensitivity and 100% specificity, comparable to previously published results [12]. Our data suggest that BHs originally prepared for definitive post-mortem diagnosis and frozen for several years are generally suitable for RT-QuIC retrospective studies; however, the presence of one negative sample confirmed that long-term storage of BH, in the form of detergent lysate, may occasionally lead to a loss of RT-QuIC seeding activity.…”
Section: Discussionsupporting
confidence: 88%
“…The sensitivity and specificity of the method are respectable. According to various studies, they range from 73% to 97% and from 99% to 100%, respectively [12]; however, the sensitivity is not 100% and there have been several cases of CJD or genetic forms of prion diseases that were not detected as positive in various studies [13,14]. The reason why these cases were not reliably detected is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no reliable fluid assays to quantify TDP-43 or -synuclein inclusions in individuals with TBI. With advances in the detection of misfolded seeds of α-synuclein in biofluids using real-time quaking-induced conversion or protein misfolding cyclic amplification (similar technologies to qualitatively detect trace amounts of diffusible misfolded α-synuclein, through its ability to induce aggregation of added recombinant αsynuclein in CSF over time, using thioflavin T fluorescence), brain -synuclein pathology can be reliably detected in lumbar CSF from patients with Parkinson's disease and other synucleinopathies (83). While so-called real-time-induced has been used to quantify TDP-43 in CSF of patients with amyotrophic lateral sclerosis and frontotemporal dementia (84), this…”
Section: Fluid Biomarkers For Tbi-related Proteinopathiesmentioning
confidence: 99%
“…Nevertheless, there are still some obstacles that need to be overcome in order for RT-QuIC to be a routine screening technique. First, the methods of these seeding assays, including a defined purification protocol for the substrate and sampling sites of peripheral tissues, must be standardized [ 260 , 261 ]. Second, the majority of studies lack autopsy-confirmed diagnosis.…”
Section: Distinct α-Synuclein Strains In Lewy Body Disease and Msamentioning
confidence: 99%